On corpus-based teaching of light verb constructions in German during foreign language lessons. Syntagmatic patterns as “instructions for use” for learners of German - Piątkowski, Łukasz (Glottodidactica, 2019)
The aim of the study is to show the possibilities of using corpus analyses for the introduction of light verb constructions in German during foreign language lessons. The corpus analyses of three selected light verb constructions Maßnahmen ergreifen, einen Beschluss fassen and Bericht erstatten show the co-occurrence of these units and enable the creation of syntagmatic patterns and the allocation of individual light verb constructions to thematic areas. The results of the analysis confirm the thesis that syntagmatic patterns are an aid to learners of German, as they present their use in a sentence and show the partner words with their syntactic function. This method can present the context of use and the thematic area of the light verb constructions. The results of the analyses are also a guideline to placing the syntagmatic patterns in German-Polish dictionaries to help learners to use them and communicate with them correctly.